2015
DOI: 10.18632/oncotarget.4692
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations caused by HNF1β expression in ovarian clear cell carcinoma contribute to cell survival

Abstract: HNF1β is expressed exclusively in ovarian clear cell carcinoma (OCCC) and not in other ovarian cancers, regarded as a hallmark of this tumor. This implies its central role in the unique character of OCCC, including resistance to chemotherapy, but its exact role and influence in cancer biology or the molecular bases of its function are largely unknown. Using comprehensive metabolome analysis of HNF1β_shRNA-stable cell lines, we show here that HNF1β drastically alters intracellular metabolism, especially in dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…It plays a role in repairing damage induced by oxidative stress in cancer cells and stops the process of cancer cachexia (36). Glutathione constitutes the survival advantage for cancer cells and is required for cancer initiation and progression (37,38). To date, a number of studies have demonstrated that the oxidant-antioxidant imbalance plays a critical role in the initiation and progression of multistage carcinogenesis of endometriosis (23,30,(39)(40)(41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a role in repairing damage induced by oxidative stress in cancer cells and stops the process of cancer cachexia (36). Glutathione constitutes the survival advantage for cancer cells and is required for cancer initiation and progression (37,38). To date, a number of studies have demonstrated that the oxidant-antioxidant imbalance plays a critical role in the initiation and progression of multistage carcinogenesis of endometriosis (23,30,(39)(40)(41).…”
Section: Resultsmentioning
confidence: 99%
“…Second, HNF-1β actually reduces and protects cancer cells from oxidative stress by markedly changing antioxidant activity (78,81,82). HNF-1β may repair damage caused by oxidative stress and can promote survival by upregulating antioxidant proteins via binding with antioxidant response element (37,68,81,83,84). This gene upregulates the synthesis of glutathione (GSH), a powerful antioxidant (85).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…To explore the intracellular metabolic change triggered by HNF1β expression, in the study in this issue of journal, we performed a comprehensive metabolite analysis (the metabolome assay) between HNF1β-high RMG2 and HNF1β_knockdown RMG2 cells [ 61 ]. As expected, repression of HNF1β expression caused drastic intracellular metabolic alteration.…”
Section: Hnf1β Drastically Alters Glycolytic Process In Occc Cellsmentioning
confidence: 99%
“…It was reported that overexpression of the glutamate-cysteine ligase catalytic subunit (GSH1) protects human ovarian cancer cells against oxidative and gamma-radiation-induced cell death [47] . Neutral and basic amino acid transport protein rBAT (SLC31) was reported to be a cysteine transporter and likely plays a major role in the increase of GSH [61] . Serum C-reactive protein (CRP) is a widely used biomarker of inflammation and has been previously shown to be a promising biomarker in patients with ovarian cancer [48] .…”
Section: Urine Proteome Changes In Nutu-19 Cell Intraperitoneal-injecmentioning
confidence: 99%